UNSTEADY MHD FLOW OF NON -NEWTONIAN FLUID WITH MASS TRANSFER IN A HORIZONTAL CHANNEL (FUDMA JOURNAL OF SCIENCES, 2022)
This study analyzes the unsteady MHD flow of non-Newtonian fluid in horizontal channel. The upper plate is oscillating and moving while the bottom plate is stationary. Solutions for momentum, energy and concentration equation are obtained by the He-Laplace scheme. The effect of various flow parameters controlling the physical situation is discussed with the aid of graphs. Significant results from this study, shows that velocity and concentric fields decrease with the increase in chemical reaction parameter
Keywords: Unsteady, MHD, Chemical reaction, Non-Newtonian fluid, He-Laplace